Empowering Communities with Media Literacy: The Critical Role of Young Children - Tomé, V.; de Abreu (2023)
This book details the project "Digital Citizenship Education for Democratic Participation" involving approximately 400 pre-school and primary school children, their families, teachers, and community members in a Lisbon locality. The research presented aims to answer the following question: To what extent can a local (and replicable) digital media literacy program empower preschool and primary-school-aged children to become active and effective citizens in the digital era? Through this book, the authors share the steps taken during the project, including the main difficulties faced and the solutions found to overcome them as well as the project’s sustainability.